Investigation of optical and electrical properties of multilayer thin films of ZnSe/ZnTe/CdSe - Y. C. Sharma, P. Ansari, R. A. Dar (International Journal of Advanced Science and Technology, 2020)
Zinc Selenide (ZnSe), Zinc Telluride (ZnTe) and Cadmium Selenide (CdSe) are II-VI semiconductors havingband gap of around 2.7eV, 2.27eV and 1.74eV, respectively. In present work multilayer ZnSe/ZnTe/CdSe thinfilms have been prepared by e-beam evaporation; having thickness 50nm/50nm/50nm to 100nm/100nm/100nm.The wavelength of 400nm-1000nm were studied by using UV-VIS spectrophotometer for optical properties of thethin films. The band gap results show the semiconducting nature of films grown. Electrical properties of thinfilms have also been studied by Current-Voltage (I-V) characteristics and Hall measurement technique.